The relationship between body mass index and the level of physical activity with anxiety caused by COVID-19 - Jalil Moradi; Mohammad Parastesh; Hossein Samadi (فصلنامه ابن سینا)
Background and aims: COVID-19 disease has a major effect on people's mental health worldwide. It is likely that in the current situation, the level of physical activity and the body mass index (BMI) status play an important role in people's mental health. The aim of this study was to investigate the relationship between BMI and the level of physical activity with anxiety caused by COVID-19 disease. Methods: The method of this study was adescriptive-correlational design, and the statistical population was all citizens of Arak city in Markazi province in 2021. The statistical sample was 486 citizens in different age groups who were selected by convenience sampling method. Participants completed the International Physical Activity Scale and the Coronavirus Anxiety Scale. Data were analysed using Pearson correlation coefficient and multivariate regression. Results: Pearson correlation results showed that there is a significant  inverse correlation between the level of physical activity and coronavirus anxiety (p<0.05). However, there is no significant relationship between BMI and coronavirus anxiety. The results of multivariate regression showed that the level of anxiety caused by coronavirus can be significantly predicted based on the level of physical activity and BMI. Conclusion: Based on the findings of the present study, it can be concluded that the increase in the level of physical activity is associated with a decrease in coronavirus anxiety. Therefore, in order to maintain the mental health of individuals in the current critical situation, it is necessary to plan for the continuation of physical activities.